2004
DOI: 10.1002/lt.20200
|View full text |Cite
|
Sign up to set email alerts
|

Liver regeneration after adult living donor and deceased donor split-liver transplants

Abstract: To the Editors:The article by Humar et al. in the March 2004 issue of Liver Transplantation is interesting in its comparison of the degree of liver regeneration, as measured by computed tomography volumetry, between living donors, living donor right-lobe recipients and split-liver recipients. 1 Their results show a significantly higher percentage increase in liver volume in left-lobe split-liver recipients (119.7%; P ϭ .0006), in right-lobe split-liver recipients (113.6%; P ϭ .01), and in right-lobe living don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Impaired liver regeneration and liver dysfunction has been strongly linked to the extent of hepatic ischemia/reperfusion injury (IRI), an unavoidable consequence of the surgical procedures, and studies in rodent models have shown that small liver fragments and SFS grafts are more susceptible to IRI (3)(4)(5)(6)(7). Although the precise mechanisms responsible for liver dysfunction and failure in small liver remnants and SFS grafts are not well understood, complement appears to play an important role in both IRI and liver regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Impaired liver regeneration and liver dysfunction has been strongly linked to the extent of hepatic ischemia/reperfusion injury (IRI), an unavoidable consequence of the surgical procedures, and studies in rodent models have shown that small liver fragments and SFS grafts are more susceptible to IRI (3)(4)(5)(6)(7). Although the precise mechanisms responsible for liver dysfunction and failure in small liver remnants and SFS grafts are not well understood, complement appears to play an important role in both IRI and liver regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Liver mass is controlled in an intriguingly exact way, which becomes essential in situations where transplanted livers that are too small for matching the body weight of the recipient have to grow until they reach their optimal size, whereas transplants that are too big in size shrink to their optimal volume (3)(4)(5).…”
mentioning
confidence: 99%
“…Although injured lobes do not regenerate in the exact identical manner, a hyperplastic response in the residual parenchyma leads to hypertrophy [ 83 ] to restore the lost mass. Typically, the liver regains the majority of its mass in about 2 weeks, regaining its function [ 84 , 85 , 86 , 87 ].…”
Section: Pathophysiology Of Liver Trauma: Local and Systemic Imbalancementioning
confidence: 99%